التنمية الاقتصادية والخدمية ودورها في تطوير وتوزيع المناطق السكنية في ليبيا - رشيد أ . أسامة محمد عبد السلام; غيثأ . رجب امحمد (Aljameai, 2022)
الملخص من الطبيعي أن تتوافر في أي تجمع سكني قائم على صعيد الريف أو الحضر أو على صعيد كافة التجمعات السكانية في الدولة دون تمييز كافة الخدمات الأساسية والبني التحتية التي تهدف إلي تطوير المجتمع وتوفير كافة المتطلبات الأساسية اللازمة لإحداث التنمية الاقتصادية المتكاملة . ومـا من شك في أن حسـن العناية بتوفير هذه الخدمات الضرورية ، وهي مسؤولية الدولة تكون لحساب المجتمع، مثلما تكون لحساب الفرد ، توطئة لرفع مستويات المعيشة في البلاد وحسن الانتفاع بهذه الخدمات وحصول الفرد على حصته فيها على اعتبـار أنه دخـل غير منظور، في حسابات مستوى المعيشة وتوفير معدلات مقبولة من الرفاهية الاقتصادية, أي أن بعد تنمية الإنسان علمياً وصحياً يصبح قادراً على العطاء لمجتمعه وبالتالي الإسهام في تنمية بلاده . والعناية برفاهية وتنمية الإنسان وهو أغلى ما تملكه أي دولة أو منطقة أو مدينة من رصيد بشري فاعل باعتباره المصدر الأساسي لإحداث التغييرات الهيكلية في كافة الأنشطة الاقتصادية والخدمية في المجتمع . ولأن حاجة المجتمع إلى توافر الخدمات الضرورية ، فينبغي تغطية احتياجات أي توسيع أو تجمع سكني أو عمراني في ليبيا من هذه الخدمات شريطة أخذ العوامل الطبيعية والبشرية في الزمان والمكان بعين الاعتبار ، وتتمثل هذه الخدمات في الخدمات الصحية التعليمية ، السيـاحية ، الطرق والمواصلات والاتصالات وغيرها. Abstract: It is natural that is available in any residential community-based rural or urban level or at the level of all communities in the country without discrimination all basic services and infrastructure which aims to develop the community and provide all needed to bring the integrated economic development of the basic requirements. There is no doubt that good care to provide these essential services, which are the responsibility of the state is to calculate the community, as they are for the account of the individual, a prelude to raise living standards in the country and good utilization of these services and get the individual to share them on the grounds that he had entered unseen, in the standard of living accounts and provide acceptable rates of economic well-being, which means that after a scientific and healthy human development is able to give to his community and thus contribute to the country’s development. And care for the welfare and development of a person, a most valuable asset of any country or region or city from the balance of a human actor as the primary source to bring about structural changes in all economic and service activities in the community. Because society is need to have the necessary services, it should cover the needs of any expansion or residential community or urban in Libya of these services are provided taking the natural and human factors in time and space in mind, and are these services in the health services, education, tourism, roads and transportation, telecommunications and others.